3rd Global Vaccine Congress. (January 2010) - Kyd, Jennelle M
Singapore was the location of the 3rd Global Vaccine Congress on 4––6 October 2009, and it provided a suitable place for sharing a range of developments, concepts and challenges associated with vaccines. One of the major goals of this meeting was to present a broad and balanced program of research, development, production, clinical testing and delivery of vaccines to people living in different parts of the world. This report contains an overview of recent developments in the vaccine field against a range of infections and disease situations that were presented during the meeting. The highlights included challenges to the current constraints on the timely and cost-effective development of vaccines and a focus on the H1N1 influenza pandemic concerns. The meeting also generated presentations that challenged the regulatory and political status quo in order to expand global access to vaccines and facilitate speedier and more cost-effective development of new vaccines.